2002
DOI: 10.1079/pns2001141
|View full text |Cite
|
Sign up to set email alerts
|

Salivary antioxidants and periodontal disease status

Abstract: Periodontal disease is a common chronic adult condition. The bacteriumPorphyromonas gingivalishas been implicated in the aetiology of this disease, which causes destruction of the connective tissue and bone around the root area of the tooth. It has been observed that invadingP. gingivalisbacteria trigger the release of cytokines such as interleukin 8 and tumour necrosis factor α, leading to elevated numbers and activity of polymorphonucleocytes (PMN). As a result of stimulation by bacterial antigens, PMN produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
136
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 36 publications
11
136
0
6
Order By: Relevance
“…In addition to having elevated temperatures, the periodontal pocket is an oxidative environment due to the presence of reactive oxygen species (Chapple, 1997;Katsuragi et al, 2003;Sculley & Langley-Evans, 2002). Consistent with reports of other organisms (Ibrahim et al, 2004;Mutunga et al, 2004;Wonderling et al, 2004), our data also suggest that the htrA-defective mutant is more susceptible to hydrogen peroxide than the wild-type.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to having elevated temperatures, the periodontal pocket is an oxidative environment due to the presence of reactive oxygen species (Chapple, 1997;Katsuragi et al, 2003;Sculley & Langley-Evans, 2002). Consistent with reports of other organisms (Ibrahim et al, 2004;Mutunga et al, 2004;Wonderling et al, 2004), our data also suggest that the htrA-defective mutant is more susceptible to hydrogen peroxide than the wild-type.…”
Section: Discussionsupporting
confidence: 81%
“…ROS have recently been reviewed in the pathogenesis of periodontitis (Canakci et al 2005). It has been suggested that as a result of stimulation by bacterial antigens, PMNs produce and release a large quantity of ROS, culminating in heightened oxidative damage to gingival tissue, periodontal ligament, and alveolar bone (Sculley and Langley-Evans 2002). ROS are active in the depolymerization of extracellular matrix components, lipid peroxidation, oxidation of enzymes such as anti-proteases, induction of pro-inflammatory cytokines, and DNA damage (Canakci et al 2005;Ozmeric 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2 More severe destructive periodontitis is associated with gum recession, loss of gingival tissue and deterioration of the underlying alveolar bone. 1 Periodontitis is an oral inflammatory disorder that causes tissue damage and loss as a result of the complex interaction between pathogenic bacteria and the host's immune response. 3 Periodontal disease is initiated by bacterial pathogens, such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans and Bacteriodes forsythus, of which P. gingivalis is the most dominant.…”
mentioning
confidence: 99%
“…3 Periodontal disease is initiated by bacterial pathogens, such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans and Bacteriodes forsythus, of which P. gingivalis is the most dominant. 1 Phagocytosis is a cellular process for destruction of antigen particles and bacteria. 4 Its system responses are divided into two pathways, oxidative and non-oxidative.…”
mentioning
confidence: 99%